Learning NHibernate 4 : explore the full potential of NHibernate to build robust data access code - Chatekar, Suhas (Community experience distilled., 2015)
This book targets .NET developers who have never used an ORM before, developers who have used an ORM before but are new to NHibernate, or have used NHibernate sparingly and want to learn more about NHibernate.